An adjustable high‐flux LED solar simulator based on dome structure - Chang‐Wen Xue; Jia‐Yong Song; Ze‐Sheng Qin; Li‐Feng Bian; Zi‐Jiang Luo; Chen Yang (Energy Science & Engineering)
Abstract High‐flux solar simulator (HFSS) commonly serves as a vital instrument for conducting material testing and thermochemical experiments, offering valuable applications in the fields of photovoltaic cells and concentrated solar energy. This paper proposes a continuously adjustable HFSS based on light‐emitting diodes (LEDs), which can be employed for experimental testing in the solar cell aging. First, an irradiation unit module has been built using high‐power LEDs and total internal reflection lenses, and the irradiation performance of the single unit has been validated. In theory, a dome layout model is proposed, in which a detailed geometric analysis is provided for the maximum number of units that can be accommodated on the dome, considering unit size and dome dimensions. Subsequently, aluminum disc has been used as thermal flux sensors, and the irradiation distribution of the system is characterized using a charge‐coupled device observation camera and Lambertian board. The results indicate that the system offers an adjustable average flux ranging from 1.6 to 9.04 kW/m2 when the system input current is in the range of 7.2–54 A. Additionally, the system demonstrates a spatial nonuniformity of 2% within a 10‐mm diameter (Φ = 10 mm) region test region and temporal instability of 2% within 30 min.